Art, Human Condition and Beyond … - Thapa, Rena (Journal of the Institute of Engineering, 2019)
Philosophers of different ages have made rigorous attempts to define art aiming to establish a set of characteristics applicable to all kinds of fine arts. However to point a definite meaning of art is elusive task. Similarly the question whether art can be didactic to provide knowledge, or insight is as old as philosophy itself. Art can be appreciated, enjoyed and loved for the powerful emotional values it reflects to the beholders. The production of art deals with creativity, imagination and innate ability of an artist. Art evolves from the culture that inspires artistic expression and art is born from the inner necessity of the artist. To determine the coherent ontological status of works of art has been a problematic issue despite the consistent philosophical practices. The metaphysical categorization of art as “the imaginary experience of the total activity" of the artist recreated by competent viewer is not all inclusive perception of art. The more liberal outlook of art as abstract cultural entities that are created at certain time through human activities seems convincing and relevant.